The effect of immunocastration and a diet based on granulated barley on growth performance and carcass, meat and fat quality in heavy gilts. (7th January 2014) - Daza, A.; Latorre, M. A.; Olivares, A.; López-Bote, C. J.
<x content-type="archive" xml:space="preserve">Abstract</x> A total of 48 Duroc×(Landrace×Large White) gilts of 33.2 kg BW were used to investigate the influence of immunocastration and diet on growth performance and carcass, meat and fat quality. Four treatments were arranged factorially (2×2) with two sexes (immunocastrated gilts: IG v. entire gilts: EG) and two dietary treatments (a commercial feedstuff as control v. granulated barley as a single major ingredient) provided during the finishing period (from 103 to 126 kg BW). There were four replicates of three pigs per treatment. At the end of the trial, the IGs grew faster (P<0.05) and ate more feed (P<0.05) than the EGs. Carcasses from the IGs had thicker backfat depth than those from the EGs (P<0.01) and carried out a lower percentage of rejected carcasses (P<0.05) at slaughterhouse owing to lack of fat. Meat from the IGs tended to have higher intramuscular fat (IMF) content in the Longissimus thoracis (LT) muscle than that from the EGs (P=0.09). In addition, immunocastration increased the total saturated fatty-acid proportion in subcutaneous fat and IMF (P<0.001) and decreased the total monounsaturated fatty acid (MUFA) and total polyunsaturated fatty acid (PUFA) percentages in subcutaneous backfat (P<0.05 and P<0.001, respectively) and in IMF (P<0.01 and P=0.06, respectively). The use of a diet based on granulated barley during the finishing period had no effect on growth performance but tended to increase IMF content in the LT muscle (P<0.06), and increased MUFA (P<0.05) and decreased PUFA (P<0.01) proportions in omental fat. It is concluded that immunocastration of gilts intended for dry-cured ham industry improved some aspects of growth performance and carcass and meat quality, whereas granulated barley had scarce effect on productive traits and fatty-acid profile but tended to improve IMF content.